2013
DOI: 10.4238/2013.september.23.6
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the endothelial nitric oxide synthase gene associated with recurrent miscarriage

et al.

Abstract: ABSTRACT. Endothelial nitric oxide synthase (eNOS) is an enzyme that influences placental human chorionic gonadotropin production during gestation. Previous studies have indicated an association between eNOS activity, implantation, and maintenance of pregnancy, but proposed associations between polymorphisms of the eNOS gene and recurrent miscarriage (RM) are controversial. To identify markers contributing to the genetic susceptibility to RM, we examined the potential association between RM and 8 single nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…Several meta-analyses revealed a close relationship between the G894T variant of the NOS3 gene and idiopathic RPL [10,17,18]. In the Chinese, there was a significant reduction in the 894G allele frequency in patients with RPL [41], corresponding to data obtained in Indian populations [38], Koreans [42], and the present study. Additionally, Shin et al found that the 894TT genotype of the NOS3 gene was significantly more common in the RPL group than in the control group (OR = 2.39; CI 1.25-4.58; p = 0.008) [42].…”
Section: Discussionsupporting
confidence: 87%
“…Several meta-analyses revealed a close relationship between the G894T variant of the NOS3 gene and idiopathic RPL [10,17,18]. In the Chinese, there was a significant reduction in the 894G allele frequency in patients with RPL [41], corresponding to data obtained in Indian populations [38], Koreans [42], and the present study. Additionally, Shin et al found that the 894TT genotype of the NOS3 gene was significantly more common in the RPL group than in the control group (OR = 2.39; CI 1.25-4.58; p = 0.008) [42].…”
Section: Discussionsupporting
confidence: 87%
“…Several reports have been showed that c.-813C>T (rs2070744) polymorphism in the 5′ flanking (promoter) region of the NOS3 gene is associated with coronary spasm and vascular disease ( Casas et al, 2006 ; Kajiyama et al, 2000 ; Nakayama et al, 1999 ; Nakayama et al, 2000 ). Also, previous studies have demonstrated the association between this polymorphism and recurrent abortions and male infertility ( Luo et al, 2013 ; Safarinejad, Shafiei, & Safarinejad, 2010 ). This SNP significantly reduces NOS3 promoter transcription activity, inhibiting NO production which ends in endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 75%
“…No association of this variant and RPL in a cohort of Tunisian had been reported [21]. Some other studies among different ethnicities after that had also reported similar ndings [22][23][24][25]. In contrast, in the study on the South Korean population had been discovered that − 786T-4b-894T haplotype signi cantly increased in the RPL group [23].…”
Section: Discussionmentioning
confidence: 85%